RISKS IN PHARMACOLOGICAL TREATMENT OF PEDIATRIC INPATIENTS–THE DOCTORś AND NURSEŚ VIEWS. Issue 1 (14th December 2015) - Lilja, Lina; Garnemark, Christiane; Kindblom, Jenny
Abstract : Background: Medication errors in pediatric care are common and clinically important. The greatest risk of error occurs during drug prescription and administration of medicines. Medication errors can be prevented if potential sources of error are identified and addressed. Objective: Explore and describe the physicians' and nurses' views on the risks regarding pharmacological treatment of pediatric inpatients. Find out what the obstacles might be for the staff in their work with prescription, preparation and administration of medicines, and what might constitute help and improvements to reduce medical errors. Method: We used three different methods to identify and describe the risks of pharmacological treatment at the department of pediatrics at Queen Silviás Children's Hospital in Gothenburg; reports from the medical error report system MedControl, targeted interviews with nurses and doctors and a questionnaire survey to all doctors and nurses. Results: The study revealed three main problem entities; difficulties related to drug prescription and the IT-system for computerized prescriptions, a need for improved support systems for drug prescriptions and administration as well as hazards relating to work environment such as disturbances, lack of time, and high staff turnover. Conclusion: Drug treatment for children is a delicate matter that places high demands on everyone involved. A pressured work environment, incomplete IT systems and gaps in supports system for drug prescription and administration are unnecessary risks. To overcome these difficulties we propose extended local prescription and administration support, coordination of procedures between wards and development of IT systems adapted to the specific needs in pediatrics.